(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Green Computing is now becoming a legislative requirement for all kind of usage in computers and digital media. Due to high spurt in the dependencies of business and education on computers and related equipment, there is a huge stress for manufacturing storage and delivery of such services. The green computing starts with the manufacturing and ends with the e-waste disposal processes so at every end care has to be taken to minimize the damage done to environment. It is a vast area but this paper limits its discussion for educational institutions only. The various green computing measures which can be taken in ICT institution are underlined. Also various green computing strategies are also discussed.